Effect of Acute Lung Injury (ALI) Induced by Lipopolysaccharide (LPS) on the Pulmonary Pharmacokinetics of an Antibody - Shweta Jogi; Dhaval K. Shah (Antibodies, 2025)
Objective: To investigate the effect of Lipopolysaccharide (LPS)-induced acute lung injury (ALI) on the pulmonary pharmacokinetics (PK) of a systemically administered antibody in mice. Method: The PK of a non-target-binding antibody was evaluated in healthy mice and mice with intratracheal instillation of 5 mg/kg LPS. The plasma, bronchoalveolar lavage (BAL), trachea, bronchi, and lung homogenate PK of the antibody were measured following intravenous administration of 5 mg/kg antibody dose. Noncompartmental analysis was performed to determine AUC values. Antibody concentrations in all biological matrices were quantified using qualified ELISA. The effect of ALI on BAL albumin and total protein concentrations was also determined. BAL protein concentrations were corrected for dilution using plasma urea concentrations. Results: Intratracheal instillation of LPS and the resultant ALI led to ~2–4-fold higher concentrations of albumin and proteins in the BAL. LPS-induced ALI also notably altered the pulmonary PK of the antibody. The effect of ALI on the antibody PK was time and tissue dependent. The trachea and bronchi showed ~1.7-fold and ~1.4-fold lower antibody exposure compared with the control group, but the BAL fluid exhibited ~4-fold increase in antibody exposure following LPS treatment. Most noticeable changes in antibody PK occurred 24 h after LPS administration, and the effect was temporary for the bronchi and trachea. However, the changes in lung homogenate and, more notably, in BAL persisted until the end of the experiment. Thus, our investigation suggests that due to the acute nature of ALI-induced pathophysiology and the changing severity of the disease, the dose and timing of antibody administration following ALI may need to be optimized based on the target site of action (e.g., bronchi, trachea, BAL, lung parenchyma, etc.) to maximize the therapeutic effect of the antibody. Conclusions: ALI may significantly affect pulmonary PK of systemically administered antibodies. Changes caused by ALI are time and tissue dependent, and hence, the timing and dose of antibody following ALI may need to be optimized to maximize the therapeutic effect of the antibody at the site of action.